Game-based Learning in TOEFL Preparatory Course - Damar Isti Pratiwi; Sri Wuli Fitriati; Issy Yuliasri; Budi Waluyo (Universitas Negeri Semarang, 2023)
The study examined the effectiveness of game-based learning in TOEFL preparatory course section 2 – structure and written expression, given over a period of 8 meetings. Employing two-cycle classroom action research design, it engaged diploma students from purposefully selected major, Railway Mechanical Technology, in Politeknik Perkeretaapian Indonesia Madiun (N=48). The first cycle learned using paper-based learning (4 meetings), and the second cycle learned using game-based learning (4 meetings). All learning processes were conducted outside classroom. The data was gathered through pretest before the first cycle and posttests after each cycle. Then, analysis was run in SPSS 25 using descriptive statistics, paired sample t-test and Cohen d to determine the degree of impact of the students’ learning outcomes. The findings showed that there was no mean difference between pretest and first cycle posttest, but there was mean difference between pretest and second cycle posttest and first cycle posttest and second cycle posttest. The test results before and after implementing game-based learning had strong relationship with modest impact. It meant that game-based learning was more effective than paper-based learning to accommodate students in TOEFL preparatory course section 2.